2018
DOI: 10.31015/jaefs.18037
|View full text |Cite
|
Sign up to set email alerts
|

Essential oil yield and compositions of chamomile (Matricaria Chamomilla L.) cultivated in different province of Turkey

Abstract: Chamom le (Matr car a chamom lla L.) is annual, herbaceous that s plant belongs to Asteraceae fam ly. The or g n of chamom le s n eastern Europe and As a M nor and t has been almost every flora of Turkey and all over the word. Chamom le s one of the important medicinal herb that has been used n herbal remed es for thousands of years. The parts of the plant used for medical purposes are flowers and the blue-green essent al o l obtained from the flowers. The most mportant essent al o l contents of chamom le are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…On the other hand, EL-Hefny et al reported cis-β-farnesene (27%) as the main component of Egyptian EO, followed by D-limonene (15.25%) and α-bisabolol oxide A (14.9%) [88]. In another study on M. chamomilla from Turkey, the EOs obtained from plants cultivated in two locations (Konya and Karaman) showed a quantitative difference in their chemical composition, with a dominance of α-bisabolol (27.36-38.6%), β-farnesene (25.05-30.15%), and chamazulene (13.5-13.93%) [89]. Furthermore, Berechet et al found that M. chamomilla EO from Romania is composed mainly of sesquiterpenes (91.65%), dominated by bisabolol oxide A (70.2%) [90].…”
Section: Phytochemical Interestmentioning
confidence: 98%
“…On the other hand, EL-Hefny et al reported cis-β-farnesene (27%) as the main component of Egyptian EO, followed by D-limonene (15.25%) and α-bisabolol oxide A (14.9%) [88]. In another study on M. chamomilla from Turkey, the EOs obtained from plants cultivated in two locations (Konya and Karaman) showed a quantitative difference in their chemical composition, with a dominance of α-bisabolol (27.36-38.6%), β-farnesene (25.05-30.15%), and chamazulene (13.5-13.93%) [89]. Furthermore, Berechet et al found that M. chamomilla EO from Romania is composed mainly of sesquiterpenes (91.65%), dominated by bisabolol oxide A (70.2%) [90].…”
Section: Phytochemical Interestmentioning
confidence: 98%